The Adherens Junction Protein Afadin Is an AKT Substrate that Regulates Breast Cancer Cell Migration - Sivan Elloul; Dmitriy Kedrin; Nicholas Knoblauch; Andrew H. Beck; Alex Toker (2013)
The PI3K-AKT signaling pathway regulates all phenotypes that contribute to progression of human cancers, including breast cancer. AKT mediates signal relay by phosphorylating numerous substrates, which are causally implicated in biologic responses such as cell growth, survival, metabolic reprogramming, migration, and invasion. Here a new AKT substrate is identified, the adherens junction protein Afadin, which is phosphorylated by AKT at Ser1718. Importantly, under conditions of physiologic IGF-1 signaling and oncogenic PI3K and AKT, Afadin is phosphorylated by all AKT isoforms, and this phosphorylation elicits a relocalization of Afadin from adherens junctions to the nucleus. Also, phosphorylation of Afadin increased breast cancer cell migration that was dependent on Ser1718 phosphorylation. Finally, nuclear localization of Afadin was observed in clinical breast cancer specimens, indicating that regulation of Afadin by the PI3K-AKT pathway has pathophysiologic significance.Phosphorylation of the adhesion protein Afadin by AKT downstream of the PI3K pathway, leads to redistribution of Afadin and controls cancer cell migration.